Vertical seismic optical profiling on wireline logging cable. (25th May 2014) - Hartog, Arthur; Frignet, Bernard; Mackie, Duncan; Clark, Mike
ABSTRACT Vertical seismic profiles are usually acquired by deploying downhole seismic sensors below a wireline logging cable. A seismic source is triggered at surface while recording the downhole vibration via the wireline cable. In this paper, an alternative approach based on distributed vibration measurement is tested using wireline deployment for the first time. Local axial strain of a multi‐kilometre fibre optic line is measured at intervals of approximately 1 m and processed to a spatial resolution of 10 m with sub nanometer strain resolution by an optical interrogation device (distributed vibration/acoustic sensing). When deployed in a well, the optical fibre line should be mechanically coupled to the borehole wall to generate valid seismic records. A conventional vertical seismic profile was acquired with three‐component sensors in a vertical well near Bottesford, UK. The impulsive seismic source was a novel portable airgun tank. Clear seismic reflections are observed within and below the borehole, in agreement with surface seismic data. A single shot generated equivalent data with an experimental optical wireline logging cable and an adequate optical interrogator at the surface. The main difference between the two records is the presence of a strong tube wave in the optical profile, which can be easily removed with conventional velocity filter processing. Corridor stacks from both conventional and optical profiles match each other and provide a reasonable tie to a nearby surface seismic line.